Force and Boldness: Cumulative Assets of a Successful Crayfish Invader - Pârvulescu, Lucian; Stoia, Dan Ioan; Miok, Kristian; Ion, Mihaela Constanţa; Puha, Adela Estera; Sterie, Melania; Vereş, Mihajel; Marcu, Ioan; Muntean, Mirela Danina; Aburel, Oana Maria (Frontiers in Ecology and Evolution, 2021)
Multiple causes can determine the disturbance of natural equilibrium in a population of a species, a common one being the presence of invasive competitors. It is well known that invasives can drive native species to the resettlement of trophic position, changing reproduction strategies or even daily normal behaviours. Here we investigated the hypothesis that more effective biological weapons of an intruder (Faxonius limosus) came with increased boldness behaviour, contributing to their invasion success in competition against the native species (Pontastacus leptodactylus). We tested boldness of specimens representing the two species by video-based assessment of crayfish individuals’ attempts to leave their settlement microenvironment. The experiment was followed by a series of measurements concerning chelae biometry, force, and muscle energetics. The native species was found less expressive in terms of boldness even if it has larger chelae and better muscular tissue performance. In contrast, because of better biomechanical construction of the chelae, the invasive species proved to be capable of twice superior force achievements, which expectedly explain their bolder behaviour. The agonistic behaviour strategy of the invasive crayfish species appears to be based on sheer physical superiority while the native crayfish relies on intimidation display. These findings suggest that, in interspecific interactions, the behaviour strategy of the invasive crayfish species is based on sheer physical superiority while the native crayfish relies on intimidation display.